2006
DOI: 10.1007/s10067-006-0343-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rheumatoid factor isotypes on disease activity and severity in patients with rheumatoid arthritis: a comparative study

Abstract: The value of rheumatoid factor (RF) isotypes for assessing rheumatoid arthritis (RA) remains debatable. In this study, we have examined the relationships between RF isotypes and disease activity and severity in RA patients. Sixty-two patients with RA, 48 women and 14 men, were studied. RF was measured by nephelometry (RF-N) and IgG-, IgA-, and IgM-RF isotypes were measured using enzyme-linked immunosorbent assay. Serum C-reactive protein and erythrocyte sedimentation rate were also determined. The patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
3
15
0
2
Order By: Relevance
“…On the other hand, the combination of positive antibodies or SE with T allele variant increases the risk of susceptibility to RA and development of erosive disease more than the sum of each separate one. The highest risk was associated with anti-CCP and RF IgG which support previous studies that showed the association of anti-CCP and RF with bone erosion in RA [37,38]. The observed interaction indicates the existence of a disease mechanism that requires the simultaneous presence of the PTPN22 1858C→T polymorphism and HLA-DRB1 SE alleles and autoantibodies.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the combination of positive antibodies or SE with T allele variant increases the risk of susceptibility to RA and development of erosive disease more than the sum of each separate one. The highest risk was associated with anti-CCP and RF IgG which support previous studies that showed the association of anti-CCP and RF with bone erosion in RA [37,38]. The observed interaction indicates the existence of a disease mechanism that requires the simultaneous presence of the PTPN22 1858C→T polymorphism and HLA-DRB1 SE alleles and autoantibodies.…”
Section: Discussionsupporting
confidence: 91%
“…В характеристике «тяжести» РА большинство авторов ставят на первое место выраженность и скорость развития деструктивного процесса в суставах [6][7][8][9], а так-же связанный с ними функциональный статус пациента [10][11][12], другие учитывают также наличие и выраженность внесуставных проявлений РА [13,14]. При этом сущест-венное место в формировании тяжести РА отводится гене-тическим, серологическим и внешнесредовым факторам (аллели системы HLA, shared epitope, изотипы РФ, антите-ла к цитруллинированному пептиду, курение и др.…”
Section: заключение изученная когорта российских больных ревматоидныunclassified
“…Наличие прогностически неблагоприятных призна-ков: активный РА с большим числом болезненных и припух-ших суставов; эрозии на ранней стадии болезни; повышение уровня РФ и/или антител к циклическому цитруллиниро-ванному пептиду (АЦЦП) [19,20], СОЭ и/или СРБ [21,22].…”
unclassified